2021
DOI: 10.1038/s41467-020-20681-4
|View full text |Cite
|
Sign up to set email alerts
|

Inositol pyrophosphates promote the interaction of SPX domains with the coiled-coil motif of PHR transcription factors to regulate plant phosphate homeostasis

Abstract: Phosphorus is an essential nutrient taken up by organisms in the form of inorganic phosphate (Pi). Eukaryotes have evolved sophisticated Pi sensing and signaling cascades, enabling them to stably maintain cellular Pi concentrations. Pi homeostasis is regulated by inositol pyrophosphate signaling molecules (PP-InsPs), which are sensed by SPX domain-containing proteins. In plants, PP-InsP-bound SPX receptors inactivate Myb coiled-coil (MYB-CC) Pi starvation response transcription factors (PHRs) by an unknown mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 61 publications
5
127
0
Order By: Relevance
“…9a, b). We found that plants carrying mutations in the PHR CC -SPX interface (AtPHR1 L331A ; L352 in OsPHR2 and AtPHR1 L339A ; L360 is OsPHR2) exhibited a growth phenotype similar to the parental phr1 phl1 line, suggesting that these mutations may disrupt the SPX -PHR complex and possibly AtPHR1 oligomerisation 25 . We thus mutated additional polar residues in the PHR CC -SPX complex interface that are located outside the AtPHR1 oligomerisation interface in the previously reported AtPHR1 CC structure 25 .…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…9a, b). We found that plants carrying mutations in the PHR CC -SPX interface (AtPHR1 L331A ; L352 in OsPHR2 and AtPHR1 L339A ; L360 is OsPHR2) exhibited a growth phenotype similar to the parental phr1 phl1 line, suggesting that these mutations may disrupt the SPX -PHR complex and possibly AtPHR1 oligomerisation 25 . We thus mutated additional polar residues in the PHR CC -SPX complex interface that are located outside the AtPHR1 oligomerisation interface in the previously reported AtPHR1 CC structure 25 .…”
Section: Introductionmentioning
confidence: 86%
“…Based on this we expressed an engineered SPX 21-202/∆47-59 construct fused to the Cterminus of the macro domain of human histone mH2A1.1 for carrier-driven crystallization 27 . The crystal structure of the mH2A1.1 181-366 tagged SPX2 1-202/∆47-59 /InsP 6 /PHR2 ternary complex was subsequently determined at 3.1 Å resolution, using InsP 6 (phytic acid) as a commercially available surrogate for the bioactive PP-InsPs 22,25 (Fig. 1a, Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphate starvation response (PSR) includes both a long-distance, systemic response that involves sensing of cellular Pi level and a local, root tip inhibition response that involves sensing of extracellular Pi availability ( Abel, 2017 ; Puga et al, 2017 ; Ried et al, 2021 ). Cellular Pi sensing relies on the MYB coiled-coil (MYB-CC) transcription factors, PHOSPHATE STARVATION RESPONSE1 (PHR1) and its related proteins PHLs ( Rubio et al, 2001 ) and inositol pyrophosphates (PP-insPs)-binding SPX proteins that exhibit Pi-dependent inhibition of PHR activities ( Puga et al, 2014 ; Wild et al, 2016 ; Ried et al, 2021 ). Under conditions of sufficient Pi, SPX binds to the coiled-coil domain of PHR and prevents the transcription factor from binding the cis -element in the promoter sequences of PSI genes and from activating their expression ( Puga et al, 2014 ; Wang et al, 2014 ; Wild et al, 2016 ).…”
Section: The Role Of Phosphate Signaling and Transport In Symbiotic Nitrogen Fixationmentioning
confidence: 99%